PENGARUH PIJAT AROMA TERAPI TERHADAP NYERI PERSALINAN DI BPS ZAHRA PUTRI PRATAMA, SST - Amrina (Akbid Wirabuana, 2022)
Background: Labor pain as an unpleasant feeling that is an individual response that accompanies in the process of labor due to changes in physiological function of the birth canal and uterus. Pain is felt very subjective and individual. Objective: To determine the effect of aromatherapy massage using lavender oil to labor pain during the first phase of activation in primigravida mother at midwife Private Practice Zahra Putri Pratama, SST, midwives Private Practice Sudilah, Amd.Keb Metro City 2018. Method: Quantitative research type, This research design is pre experiment with One Group Pre-test approach - Post-test Design. The population in this study is the total of pregnant women aterem in April at BPS Zahra and Sudilah as many as 30 pregnant women. The sample in this study amounted to 24 people. Sampling in this research by accidental sampling. Data collection using observation sheets. The analysis used t-test dependent test statistic. Known average labor pain before given with average score value of labor pain frequency 6.62 With Severe Pain. Known Average Pain of labor after being given with an average score score of the frequency of labor pain 3.62 With Moderate Pain. There was an effect of lavender aromatherapy massage on the active stage I labor phase with P-Value 0.000 value. It is expected that midwives can apply to every patient who will give birth so that the labor pain that the mother can feel is reduced by massage using lavender aromatherapy.